Exciting vibrons in both frontier orbitals of a single hydrocarbon molecule on graphene. (24th December 2018) - Mehler, A; Néel, N; Bocquet, M-L; Kröger, J
Abstract: Vibronic excitations in molecules are key to the fundamental understanding of the interaction between vibrational and electronic degrees of freedom. In order to probe the genuine vibronic properties of a molecule even after its adsorption on a surface appropriate buffer layers are of paramount importance. Here, vibrational progression in both molecular frontier orbitals is observed with submolecular resolution on a graphene-covered metal surface using scanning tunnelling spectroscopy. Accompanying calculations demonstrate that the vibrational modes that cause the orbital replica in the progression share the same symmetry as the electronic states they couple to. In addition, the vibrational progression is more pronounced for separated molecules than for molecules embedded in molecular assemblies. The entire vibronic spectra of these molecular species are moreover rigidly shifted with respect to each other. This work unravels intramolecular changes in the vibronic and electronic structure owing to the efficient reduction of the molecule–metal hybridization by graphene.